Reply letter to the editor concerning the article 'Safety of Sars-Cov-2 vaccines administration for adult patients with hereditary fructose intolerance' - Elsa Izquierdo-Garcia; Elena Alba Alvaro Alonso; Berta Montero Pastor; Ana Such Díaz; Ismael Escobar Rodríguez (Taylor & Francis Group, 2022)
According to the current European medicines legislation, on the labeling is mandatory a warning contraindicating for hereditary fructose intolerance (HFI) patients medicines with oral or parenteral fructose and sorbitol, and oral sucrose, invert sugar, isomaltitol, lactitol and maltitol, but parenteral sucrose is not mentioned. Intravenous administration of sucrose does not increase blood glucose concentrations, because sucrose is poorly oxidized to CO2 and mainly excreted in the urine as a disaccharide; absence of enzimatic activity outside the gut explains why there is not a warning for parenteral sucrose presentations. For this reason, parenteral drugs with sucrose are allowed in HFI patients. Nevertheless, due to interindividual variability and the fact that not all parenterally administered sucrose is recovered in urine, HFI patients need to be closely monitored after parenteral administration of sucrose-containing drugs, especially when the amount exceeds the maximum permissible thresholds.